Return to sport after conservative treatment of elbow dislocation in judoka - Lambert, Christophe; Ritzmann, Ramona; Geßlein, Markus; Bouillon, Bertil; Höher, Jürgen; Akoto, Ralph; Wafaisade, Arasch (Sportverletzung · Sportschaden, 2023)
Background Injuries to the elbow are frequent in judo combat, but studies on down-time and effect on performance after conservative treatments are rare. This issue is particularly relevant for elbow dislocations in high-performance patients such as elite athletes. The purpose of this study was to evaluate (1) time-loss and (2) the regained level of performance in judoka after conservative treatment of simple elbow dislocation.Methods In cooperation with the European Judo Union, judoka were asked to complete a 139-item survey regarding elbow injuries they suffered during their career. Besides demographics, injury data, diagnosis and treatment options, the athletes were asked about down-time and reductions in performance level. This study enrolled 108 judoka with conservative treatment of elbow dislocation out of a population of 5426 volunteers.Results 69% (n=74) reported a time-loss of less than three months; 6% reported a time-loss of more than six months. The majority (68%, n=73) reported that they had returned to their previous performance level, while 22% (n=24) suffered from a slightly reduced level of performance. In the subgroup of international and national athletes (n=54), 63% returned to judo after less than three months, with 72% achieving the same level and 15% reporting a slightly reduced performance level. Level of performance and time lost after conservative treatment for elbow dislocations were comparable for male and female judoka.Conclusion Approximately two out of three judoka returned to the same level of performance after three months of down-time after undergoing conservative therapy for simple elbow dislocations. Despite the high performance level of the study population, conservative treatment of simple elbow dislocation resulted in satisfactory outcomes. The presented data can guide medical professionals and competitive-level contact-sport athletes with respect to expectations in the process of returning to sport.
Keywords: Ellenbogenluxation; Olympischer Sport; Rückkehr zum Sport; Sportverletzungen; Judo